The Golden Hour: Early Interventions for Medical Emergencies during Pregnancy - Pacheco, Luis D.; Lozada, M. J.; Saade, George R. (American Journal of Perinatology, 2020)
Maternal mortality has increased in the last decades in the United States as a result of increased prevalence of coexisting medical diseases such as hypertension, diabetes, and both acquired and congenital heart diseases. Obstetricians and maternal–fetal medicine physicians should have the basic medical knowledge to initiate appropriate diagnostic and early therapeutic interventions since they may be the only provider available at the time of presentation. The goal of this article is not to extensively discuss the management of complex medical diseases during pregnancy, rather we provide a concise review of key early medical interventions that will likely result in improved clinical outcomes.Key Points
Keywords: pregnancy; medical diseases; medical emergencies